Wage Setting, Social Pacts and the Euro A New Role for the State - Hassel, Anke (Changing Welfare States, 2006)
Globalization, financial liberalization and neo-liberal economic policy thinking have been seen as contributors to the demise of social partnership in Western Europe. Recent examples of the re-emergence of social pacts have challenged these assumptions. The book offers a theoretical understanding of the challenges that increasing monetary integration posed for existing modes of adjustment in the political economies of EU member states, and explains why many governments have chosen to negotiate with trade unions over economic adjustment.